Scavenging Capacity of Extracts of Arrabidaea chica Leaves from the Amazonia against ROS and RNS of Physiological and Food Relevance - Francilia Campos de Siqueira; Anna Paula Pereira Barbosa-Carvalho; Deusa do Socorro Teixeira Costa Leitão; Kalebe Ferreira Furtado; Gilson Celso Albuquerque Chagas-Junior; Alessandra Santos Lopes; Renan Campos Chisté (MDPI AG, 2022)
Arrabidaea chica, a medicinal plant found in the Amazon rainforest, is a promising source of bioactive compounds which can be used to inhibit oxidative damage in both food and biological systems. In this study, the in vitro scavenging capacity of characterized extracts of A. chica leaves, obtained with green solvents of different polarities [water, ethanol, and ethanol/water (1:1, v/v)] through ultrasound-assisted extraction, was investigated against reactive oxygen (ROS) and nitrogen (RNS) species, namely superoxide anion radicals (O2•−), hydrogen peroxide (H2O2), hypochlorous acid (HOCl), and peroxynitrite anion (ONOO−). The extract obtained with ethanol-water presented about three times more phenolic compound contents (11.8 mg/g) than ethanol and water extracts (3.8 and 3.6 mg/g, respectively), with scutellarein being the major compound (6.76 mg/g). All extracts showed high scavenging efficiency against the tested ROS and RNS, in a concentration-dependent manner with low IC50 values, and the ethanol-water extract was the most effective one. In addition, all the extracts were five times more efficient against ROO• than Trolox. Therefore, the extracts from A. chica leaves exhibited high promising antioxidant potential to be used against oxidative damage in food and physiological systems.